2015
DOI: 10.1186/s13705-015-0043-y
|View full text |Cite
|
Sign up to set email alerts
|

Fuel value indices of selected woodfuel species used in Masindi and Nebbi districts of Uganda

Abstract: Background: Biomass currently meets more than 97% of the total energy requirements in Uganda. However, contrary to this heavy reliance on biomass, there is paucity of information regarding the fuel value indices (FVIs) of woodfuel species used in different locations of the country such as Masindi and Nebbi districts. This study therefore sought to identify ten woodfuel species commonly used by the communities in these two districts and examine their FVIs from basic properties, namely; moisture content, density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 18 publications
6
19
1
Order By: Relevance
“…This is in conformity with what was reported on woods and barks of some biomass by Deka, et al [9] and Nosek, et al [13]. Different studies have demonstrated the influence of moisture content on the combustion properties of fuelwood materials [24][25][26][27][28] and concluded that moisture had negative effect on fuel value of the wood. Thus, bio fuel materials with low moisture content are always preferred because of the high energy content per unit volume, durability and slow burning rate.…”
Section: Moisture Content (Mc)supporting
confidence: 90%
“…This is in conformity with what was reported on woods and barks of some biomass by Deka, et al [9] and Nosek, et al [13]. Different studies have demonstrated the influence of moisture content on the combustion properties of fuelwood materials [24][25][26][27][28] and concluded that moisture had negative effect on fuel value of the wood. Thus, bio fuel materials with low moisture content are always preferred because of the high energy content per unit volume, durability and slow burning rate.…”
Section: Moisture Content (Mc)supporting
confidence: 90%
“…A. grandibracteata species mostly grow in the upland rainforest and riverine forest areas, with preference in moist and wet sites. This tree species is known for its multiple provisional services [35]. It provides multiple socio-economic benefits (firewood, farm tools, medicine from the root, bee forage, ornamental, and soap from its bark); it is also known for nitrogen fixation which is one of its ecological services [32].…”
Section: Species Descriptionmentioning
confidence: 99%
“…Reasons given for this low uptake are the difficulties of implementation and control within the overall informal sector, the relatively high investment costs of improved kiln types, the impracticality of having a stationary kiln while lacking means of transporting the wood and the lack of skills and training to construct or operate the kilns (van Beukering et al, 2007;GIZ, 2015;Iiyama et al, 2014;Smeets et al, 2012). The efficiency of carbonisation depends not only on the type of kiln used, but also on other factors, notably wood properties, including wood moisture, wood density and diameter log, and skills of producers in efficient kiln construction, involving drying of the wood, proper wood arrangement and monitoring of the carbonisation process (Antal and Grønli, 2003;Kammen and Lew, 2005;Malimbwi et al, 2000;Ojelel et al, 2015).…”
Section: Efficiency Of Charcoal Production In Sub-saharan Africamentioning
confidence: 99%